The folds of Olympus : mountains in ancient Greek and Roman culture - König, Jason (Princeton scholarship online, 2023)
The mountainous character of the Mediterranean was a crucial factor in the history of the ancient Greek and Roman world. 'The Folds of Olympus' is a cultural and literary history that explores the important role mountains played in Greek and Roman religious, military, and economic life, as well as in the identity of communities over a millennium - from Homer to the early Christian saints. Aimed at readers of ancient history and literature as well as those interested in mountains and the environment, the book offers a powerful account of the landscape at the heart of much Greek and Roman culture